Thermal aging resistance of natural rubber compounded with conjugated Schiff base - Wang, Jianfa; Gu, Zheng; Zhang, Susu; Wang, Ning; Sui, Jinyong; Zhang, Xiaoyi; Li, Peiyao; Liu, Wenjin; Hu, Yifan (Polimery, 2022)
Schiff’s base iron salt can be used as a new and effective antioxidant for rubber compounds. The tensile strength after 96 h of aging was approx. 36% and 12% higher, respectively, than in the case of the antioxidants 4010NA and BHT used. Natural rubber vulcanizate (NR) containing the iron salt of Schiff’s base showed excellent rheological and mechanical properties, as well as very good thermal stability. These properties were far superior to that of other commercially available antioxidant rubber blends.